Volumetric analysis of Hand and Rotary instrumentation and Evaluation of Obturating material in Primary teeth using CBCT – A Clinical trial - Anumukonda Rohitha Sravya; Balagopal Varma R; Suresh Kumar J; Parvathy Kumaran; Arun M Xavier; Malini Venugopal; Nishna Thankappan (The Bioscan, 2024)
Aims & Background: The biomechanical preparation is considered a critical step in the Pulpectomy procedure. The goal is to remove the microbiological contents in the canal and protect tooth function. In-vitro studies demonstrate that the shape of the root canal is more conical, favouring higher obturation quality and thereby increasing success rate using rotary files. So, this clinical trial aims to compare the volume of root canals before and after root canal instrumentation using hand and rotary files and to evaluate the flow of obturating material using CBCT in primary molars. Materials and Methods: This trial was conducted in 20 primary molars which were assigned to Group 1 (Hand files) and Group 2 (Rotary files). A CBCT was taken at 3 different intervals i.e., Prior to the procedure, After BMP, After the procedure. The difference between the Pre-instrumentation and Post-instrumentation CBCT images reveals the 3D volume change measured using hand and rotary files. Post-instrumentation and Post-obturation CBCT scans display the flow of root canal filling material in primary molars. Results: There were statistically significant differences noticed within Group 1 (p value = 0.000); and pre-instrumentation and post-instrumentation, pre-instrumentation and post-obturation in Group 2 (p value = 0.000). No statistically significant difference seen between post-instrumentation and post-obturation values (p value = 0.076). Significant differences were found in post-instrumentation and post-obturation volumes between groups. Conclusion: This trial concluded that rotary files led to a more productive funnel-shaped canal preparation that resulted in better obturation quality with minimal voids than hand files. Clinical significance: Rotary files using 3D imaging allowed more conservative and efficient root canal preparation while maintaining anatomy, resulting in superior three-dimensional obturation than hand files.